2016
DOI: 10.3390/s16060852
|View full text |Cite
|
Sign up to set email alerts
|

Quality Detection of Litchi Stored in Different Environments Using an Electronic Nose

Abstract: The purpose of this paper was to explore the utility of an electronic nose to detect the quality of litchi fruit stored in different environments. In this study, a PEN3 electronic nose was adopted to test the storage time and hardness of litchi that were stored in three different types of environment (room temperature, refrigerator and controlled-atmosphere). After acquiring data about the hardness of the sample and from the electronic nose, linear discriminant analysis (LDA), canonical correlation analysis (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…The electronic nose detection has the advantages of being fast, simple and non-destructive [8]. Ying [9] and Xu [10] respectively used e-nose to evaluate the freshness of litchi and measured the storage time of litchi under three different conditions. Dai [11] combined electronic nose with headspace solid phase microextraction (HS-SPME)-GC-MS to analyze the volatile components in the fermentation process of Tremella aurantialba.…”
Section: Introductionmentioning
confidence: 99%
“…The electronic nose detection has the advantages of being fast, simple and non-destructive [8]. Ying [9] and Xu [10] respectively used e-nose to evaluate the freshness of litchi and measured the storage time of litchi under three different conditions. Dai [11] combined electronic nose with headspace solid phase microextraction (HS-SPME)-GC-MS to analyze the volatile components in the fermentation process of Tremella aurantialba.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic nose, simulated sense of smell in mammals, has been widely used in research field of food flavor, such as mushroom (Yang et al, ), beef fillets (Papadopoulou, Panagou, Mohareb, & Nychas, ), and edible oils (Xu, Yu, et al, ) and has become an important method for its feasibility and sensitivity. Responses of ten sensors of electronic nose to fresh tomato pulp are presented in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…They found that LDA provides better performance with an accuracy of 98.21% and discriminate the different stages of incubation and invasion. Xu et al (2016) used PEN3 E-nose predicts to litch quality. Litch quality was detected in different environments (normal temperature, refrigerator, controlled condition).…”
Section: Fruits and Vegetables Quality Prediction Using Electronic Nosementioning
confidence: 99%